Podocalyxin‐Like Protein 1 Regulates Pluripotency through the Cholesterol Biosynthesis Pathway. Issue 1 (14th November 2022) - Chen, Wei‐Ju; Huang, Wei‐Kai; Pather, Sarshan R.; Chang, Wei‐Fang; Sung, Li‐Ying; Wu, Han‐Chung; Liao, Mei‐Ying; Lee, Chi‐Chiu; Wu, Hsuan‐Hui; Wu, Chung‐Yi; Liao, Kuo‐Shiang; Lin, Chun‐Yu; et al.
Abstract: Deciphering signaling mechanisms critical for the extended pluripotent stem cell (EPSC) state and primed pluripotency is necessary for understanding embryonic development. Here, a membrane protein, podocalyxin‐like protein 1 (PODXL) as being essential for extended and primed pluripotency, is identified. Alteration of PODXL expression levels affects self‐renewal, protein expression of c‐MYC and telomerase, and induced pluripotent stem cell (iPSC) and EPSC colony formation. PODXL is the first membrane protein reported to regulate de novo cholesterol biosynthesis, and human pluripotent stem cells (hPSCs) are more sensitive to cholesterol depletion than fibroblasts. The addition of exogenous cholesterol fully restores PODXL knockdown‐mediated loss of pluripotency. PODXL affects lipid raft dynamics via the regulation of cholesterol. PODXL recruits the RAC1/CDC42/actin network to regulate SREBP1 and SREBP2 maturation and lipid raft dynamics. Single‐cell RNA sequencing reveals PODXL overexpression enhanced chimerism between human cells in mouse host embryos (hEPSCs 57%). Interestingly, in the human–mouse chimeras, laminin and collagen signaling‐related pathways are dominant in PODXL overexpressing cells. It is concluded that cholesterol regulation via PODXL signaling is critical for ESC/EPSC. Abstract : Cholesterol is important for membrane composition and cell division. Chen et al. show that PODXL regulates de novo cholesterol biosynthesis and further sustains the primed and extended renewal states in hPSCs through c‐MYC, TERT, and ITGA2. PODXL overexpression facilitates the extended pluripotency state in vitro and in vivo. These data highlight that PODXL links cellular metabolism to stem cell self‐renewal.